2019
DOI: 10.1080/15592324.2019.1686236
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation: another layer in plant nutrition

Abstract: Uptake, assimilation, and recycling of nutrients are essential for optimal plant growth and development. A large number of studies have contributed significantly to highlight the major features that shape an efficient utilization of nutrients in plants, especially at the transcriptional level. However, only a few examples have explored the epigenetic mechanisms that are intrinsically associated to the transcriptional reprogramming events in response to nutritional fluctuations. In this review, we gather the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…At the molecular level, plants respond to nutritional status by modulating gene expression at multiple levels through a network of transcription factors and via post-translational regulation. Multiple studies have also revealed that changes in chromatin state by histone modification or DNA methylation play important roles in nutrient homeostasis in plants (Secco et al, 2017;Séré and Martin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, plants respond to nutritional status by modulating gene expression at multiple levels through a network of transcription factors and via post-translational regulation. Multiple studies have also revealed that changes in chromatin state by histone modification or DNA methylation play important roles in nutrient homeostasis in plants (Secco et al, 2017;Séré and Martin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Histone methylation is a repressive mark placed by the Polycomb Repressive Complex 2 (PRC2). The histone methylation pattern is altered under Fe excess in roots; the repressive marks arginine dimethylation H4Arg3me2 and lysine trimethylation H3Lys27me3 induced the suppression of the Fe acquisition system ( Séré and Martin, 2020 ). In the shoot, under conditions of Fe excess, PRC2 targets YSL1 and IRON MAN1 , both of which are involved in long-distance Fe signalling ( Kumar et al , 2017 ; Grillet et al , 2018 ).…”
Section: Information On the Intracellular Iron Status In Leavesmentioning
confidence: 99%
“…Recent studies have highlighted the importance of epigenetic regulation in modulating nitrogen metabolism and the plant response to nutrient availability (Sere and Martin, 2020). SET DOMAIN GROUP 8 (SDG8) regulates the N assimilation and lateral root response by regulating H3K36me3 level in response to changing N levels in Arabidopsis (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%